Ability of Escherichia coli to form biofilm in tomato fruits (Solanum lycopersicum L.) - ROJAS PUEBLA, Itzel; OCAÑA DE JESÚS, Rosa Laura; AHUMADA COTA, Ricardo Ernesto; ESLAVA CAMPOS, Carlos Alberto; HERNÁNDEZ CHIÑAS, Ulises; LÓPEZ SANDOVAL, José Antonio; GUTIÉRREZ IBÁÑEZ, Ana Tarin (Food Science and Technology, 2025)
Foodborne diseases are frequently caused by bacterial pathogens, many of which are able to protect themselves from unfavorable environmental conditions by forming a biofilm, allowing them to successfully colonize inert surfaces and living substrates, such as edible fruits. The objective of this study was to evaluate the formation of biofilms by Escherichia coli from different origins (12 strains) in order to select the best biofilm formers and investigate them on tomato fruits under greenhouse conditions. For this purpose, the microtiter technique was used, which permits measuring the adhesion of bacterial communities to surfaces. Two media were assessed (minimum essential added with glucose and Luria Bertanni broth), incubated at 37°C, and readings were taken at 24, 48 and 72 hours. The results showed that the strains differed in their biofilm production levels, with no difference between the media evaluated, reaching their maximum production level at 72 hours. The bacteria with the best production were enterohemorrhagic O157:H7, which were inoculated on tomatoes for evaluation prior to greenhouse conditions, where biofilm development was determined at two production stages (commercial and physiological maturity). The results demonstrated that Escherichia coli has the ability to form biofilms on tomato fruits.